Assessing The Impacts of Community-Based Technical Education and Training Projects in Northern Malaysia - Sharifah, Syahirah; Osman, Syamsul Fozy; Amat@Adnin, Norfarahin; Mohamed Roseli, Nurul Rashidah (Journal of Technical Education and Training, 2023)
Leaving no one behind is the central transformative promise of the 2030 Agenda of Sustainable Development Goals (SDGs). In Malaysia, the formation of the All-Party Parliamentary Group Malaysia on the Sustainable Development Goals (APPGM-SDG) by the Malaysian Parliament has made it possible to localise this SDGs’ transformative agenda. Therefore, this paper attempts to discuss the effectiveness of programs conducted by solution providers in the Northern region in managing and conducting projects, the impact of the projects on the beneficiaries, the alignment and mapping of the impact evaluations of the solution providers with the SDG goals and APPGM-SDG modules, and identification of issues and recommended solutions to the projects in the Northern region. Twenty-three (23) APPGM-SDGs projects were implemented from 2021 to 2022, consisting of various programs, mainly entrepreneurship, environment, research and education. As a bipartisan initiative to localise SDG goals in Parliamentary constituencies in Malaysia, it is crucial to analyse the impact of its implementation. Hence, this study has conducted an impact evaluation analysis from October 2022 until January 2023 in seven (7) constituencies in Kedah, Penang and Perak. Using four (4) dimensions of impact analysis framework, which are psychology and knowledge, skills, network, and system of these projects on the beneficiaries to determine the effectiveness of each project. This study has collected data from document analysis, focus group discussion and site-visit to the twenty-three (23) projects in the Northern Region. The findings indicate the programmes were well-implemented and beneficiaries managed to learn new skills and strengthen their networks.